High-Performance Metal-Supported Solid Oxide Fuel Cells by Advanced Cathode Processing. Issue 13 (5th October 2017) - Udomsilp, D.; Roehrens, D.; Menzler, N. H.; Bischof, C.; de Haart, L. G. J.; Opitz, A. K.; Guillon, O.; Bram, M.
Abstract : La0.58 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathodes on metal-supported solid oxide fuel cells (MSCs) were fabricated by a novel sintering approach and electrochemically tested in single-cell measurements. The sintering of cathodes on complete cells was performed under argon atmosphere at 950°C in order to prevent strong oxidation of the metallic support. During this sintering process, a phase decomposition of LSCF occurred, which was found to be reversible upon heating in ambient air. The observed performance increase of MSCs with cathodes sintered ex situ, compared to cells processed under standard conditions, revealed a beneficial effect of the increased sintering temperature on cell performance. At 750°C and 0.7 V a current density of 0.96 A/cm 2 was achieved. A stronger adherence of the cathodes sintered ex situ was observed after single-cell measurements. In additional experiments, La0.58 Sr0.4 CoO3-δ (LSC) was applied as an alternative cathode for MSCs. These cells were activated in situ at 850°C due to the lower thermochemical stability of LSC and indicated potential for further improvement of the cell performance. The successful electrochemical characterization of the cells with LSCF cathodes sintered ex situ confirmed the applicability of the novel sintering procedure as well as the improved adherence achieved by the optimized processing.